Analisis Efektivitas Pelatihan Terhadap Keterampilan Petani di UPT Pelatihan Pertanian Lawang Kabupaten Malang Menggunakan Model Kirkpatrick - Anwar, Nadhif Syathiril; Hendrarini, Hamidah; Yuliati, Nuriah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The role of agricultural training is very important, especially considering the decreasing number of government extension workers in the field and the lack of interest of young people in agriculture. Through training, farmers can improve their competence in skills, expertise, and knowledge in the field of agriculture. Training/education and training at the UPT which focuses on processing vegetable crops uses a learning system with concepts and analysis and with the existing curriculum and is supplemented with the support of learning and practice facilities and infrastructure provided by the training instructor. The purpose of this study was to analyze the effectiveness of training on the skills of its training participants. This research method uses the Kirkpatrick model as a measuring tool to determine whether the training is effective or not which consists of 4 levels, namely: evaluation of reactions, learning, behavior, and results. The respondent sample used the census method, namely all participants totaling 30 people. The results of the Kirkpatrick model research show a high level of participant satisfaction with the training materials, methods, and facilitators (reactions), a significant increase in participant knowledge and skills based on the results of the pre-test and post-test (learning), positive changes in the application of knowledge in the field (behavior), and a real impact on increasing the productivity and management of participants' farming businesses (results).